An Evocative Translation and Theology of the Hebrew לְרוּחַ הַיּוֹםin Genesis 3:8 - Henry Sitanggang (Fakultas Filsafat Universitas Advent Indonesia, 2022)
This study has examined the Hebrew expression לְרוּחַ הַיּוֹם,